Medical loss ratio as a potential regulatory tool in the Israeli healthcare system. Issue 1 (December 2015) - Simon-Tuval, Tzahit; Horev, Tuvia; Kaplan, Giora
Abstract Background The growth of the private health insurance sector in Western countries, which is characterized by information deficiencies and limited competition, necessitates the implementation of effective regulatory tools. One measure which is widely used is the medical loss ratio (MLR). Our objective was to analyze how MLR is applied as a regulatory measure in the Israeli voluntary health insurance (VHI) market in order to promote the protection of beneficiaries. The study will examine MLR values and the use of this tool by regulators of VHI in Israel. Methods Descriptive analysis using 2005–2012 data from public reports of the Ministry of Health and the Ministry of Finance on VHI plans in three market segments: nonprofit health plans, group (collective) policies offered by commercial insurance companies and individual policies offered by commercial insurance companies. Results In 2012, 74% of the Israeli population owned VHI provided by nonprofit health plans and 43% owned VHI offered by for-profit commercial companies. At that time the MLRs of three nonprofit health plans were significantly lower than 80%, mostly in the upper layers of coverage. The MLR in the individual commercial segment was consistently low (38% in 2012). The use of MLR as a regulation tool was, and continues to be, relatively limited in all segments. Conclusion The VHI in Israel covers several essential services that are not covered by the statutory benefits package as a result of budget constraints. Thus, due to the high penetration rate of VHI in Israel compared to European countries and the lower levels of MLR, in order to assure the protection of beneficiaries it may be warranted to increase the extent of regulation and adjust it to the nature of the services covered. This may include distinguishing between essential and nonessential coverages and implementation of the most suitable regulatory measures (such as an MLR threshold, limitation of services covered and adjusting the actuarial models to the beneficiaries' behavior), rather than focusing only on assuring solvency.